An Islamic philosophy of virtuous religions : introducing Alfarabi - Parens, Joshua, 1961- (State University of New York Press, 2006)
"Joshua Parens provides an introduction to the thought of Alfarabi, a tenth-century Muslim political philosopher whose writings are particularly relevant today. Parens focuses on Alfarabi's Attainment of Happiness, in which he envisions the kind of government and religion needed to fulfill Islam's ambition of universal acceptance. Parens argues that Alfarabi seeks to temper the hopes of Muslims and other believers that one homogeneous religion might befit the entire world and counsels acceptance of the possibility of a multiplicity of virtuous religions. Much of Alfarabi's approach is built upon Plato's Republic, which Parens also examines in order to provide the necessary background for a proper understanding of Alfarabi's thought."--Jacket.